Case report: Germline POT1 mutation in a patient with GIST and lung adenocarcinoma - Martino, Stefania; De Summa, Simona; Pilato, Brunella; Digennaro, Maria; Laera, Letizia; Tommasi, Stefania; Patruno, Margherita (Frontiers in Oncology, 2024)
The gene protection of telomere 1 (POT1) is involved in telomere maintenance and stability and plays a crucial role in the preservation of genomic stability. POT1 is considered a high-penetrance melanoma susceptibility gene; however, the number of cancer types associated with the pathogenic germline variants of POT1 is gradually increasing, including chronic lymphocytic leukemia (CLL), angiosarcomas, and gliomas, even though many associations are still elusive. Here, we reported a case of a 60-year-old man who showed early-onset multiple neoplasms, including multiple melanomas, gastrointestinal stromal tumor (GIST), and lung adenocarcinoma. Next-generation sequencing (NGS) analyses revealed a germline heterozygous pathogenic variant in the POT1 gene. Notably, GIST and lung adenocarcinoma were not previously reported in association with the POT1 germline variant. Lung cancer susceptibility syndrome is very rare and the actual knowledge is limited to a few genes although major genetic factors are unidentified. Recently, genome-wide association studies (GWAS) have pointed out an association between POT1 variants and lung cancer. This case report highlights the clinical relevance of POT1 alterations, particularly their potential involvement in lung cancer. It also suggests that POT1 testing may be warranted in patients with familial cancer syndrome, particularly those with a history of melanoma and other solid tumors.